SRNA‐pathway genes regulating myxobacterial development exhibit clade‐specific evolution. Issue 2 (14th February 2019) - Chen, I‐Chen Kimberly; Satinsky, Brandon M.; Velicer, Gregory J.; Yu, Yuen‐Tsu Nicco
Abstract : Small non‐coding RNAs (sRNAs) control bacterial gene expression involved in a wide range of important cellular processes. In the highly social bacterium Myxococcus xanthus, the sRNA Pxr prevents multicellular fruiting‐body development when nutrients are abundant. Pxr was discovered from the evolution of a developmentally defective strain (OC) into a developmentally proficient strain (PX). In OC, Pxr is constitutively expressed and blocks development even during starvation. In PX, one mutation deactivates Pxr allowing development to proceed. We screened for transposon mutants that suppress the OC defect and thus potentially reveal new Pxr‐pathway components. Insertions significantly restoring development were found in four genes— rnd, rnhA, stkA and Mxan_5793 —not previously associated with an sRNA activity. Phylogenetic analysis suggests that the Pxr pathway was constructed within the Cystobacterineae suborder both by co‐option of genes predating the Myxococcales order and incorporation of a novel gene ( Mxan_5793 ). Further, the sequence similarity of rnd, rnhA and stkA homologs relative to M. xanthus alleles was found to decrease greatly among species beyond the Cystobacterineae suborder compared to the housekeeping genes examined. Finally, ecological context differentially affected the developmental phenotypes of distinct mutants, with implications for the evolution of development in variable environments.